2018
DOI: 10.1111/add.14478
|View full text |Cite
|
Sign up to set email alerts
|

The public health consequences of e‐cigarettes: a review by the National Academies of Sciences. A call for more research, a need for regulatory action

Abstract: Electronic nicotine delivery systems (ENDS) are less harmful than combustible cigarettes but lack demonstrated safety. They may help some smokers to quit, while enticing future generations to smoke. The US regulatory environment has restricted research on ENDS for tobacco cessation yet extended the time for open market sales. Calls for further research ought not to stall regulatory action.Electronic nicotine delivery systems (ENDS; e.g. ecigarettes) have gained world-wide attention. Gaps in the evidence on END… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 10 publications
1
34
0
5
Order By: Relevance
“…Flavours increase product attractiveness among all types of (potential) users, that is, among youth and adults8 and among current smokers, dual users, exclusive vapers, as well as never-users 9. For smokers, switching to e-cigarettes may be beneficial, as e-cigarette use (ie, vaping) is considered less harmful than regular cigarette smoking 10–14. In line with this, the use and marketing of e-liquid flavours that are appealing to smokers may contribute to public health benefits.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Flavours increase product attractiveness among all types of (potential) users, that is, among youth and adults8 and among current smokers, dual users, exclusive vapers, as well as never-users 9. For smokers, switching to e-cigarettes may be beneficial, as e-cigarette use (ie, vaping) is considered less harmful than regular cigarette smoking 10–14. In line with this, the use and marketing of e-liquid flavours that are appealing to smokers may contribute to public health benefits.…”
Section: Introductionmentioning
confidence: 98%
“…However, flavours may also stimulate vaping among non-users, in particular young people 15–17. This is concerning, as e-cigarettes are not safe10 18 19 That is, chemicals in e-cigarette emissions (eg, tobacco-specific nitrosamines, metals, aldehydes and other flavourings) can be toxic and thus harmful to consumers’ health 20–22. In addition, e-cigarettes may facilitate smoking initiation among never-smokers 23.…”
Section: Introductionmentioning
confidence: 99%
“…Third, Altria recently bought 35% of Juul, the manufacturers of highly addictive nicotine vaping that has caused an epidemic of nicotine addiction among American youth. The National Academies of Sciences, Engineering and Medicine concluded that e‐cigarettes may be harm‐reducing for smokers seeking to quit combustible tobacco, while harm‐creating for former or never smokers. Simulations to 2070 suggest that e‐cigarette use will not diminish the overall burden of disease.…”
Section: A Few News Stories In the Order Retrieved From Google News Smentioning
confidence: 99%
“…Alarmingly, from 2017 to 2018 alone, there was a 75% increase in ENDS use by high school students 1 . The popularity of flavored ENDS likely fueled the proliferation of manufacturers, and the surge in sales of these products 2 . In 2014, it was estimated that there were more than 7600 different flavored ENDS products from 466 brands 3 , and as of this date, these numbers have only increased.…”
Section: Introductionmentioning
confidence: 99%